Capsule Homology Does Not Increase the Frequency of Transformation of Linked Penicillin Binding Proteins PBP 1a and PBP 2x in Streptococcus pneumoniae - Trzciński, Krzysztof (American Society for Microbiology, 2005)
Penicillin resistance is mainly confined to a limited number of Streptococcus pneumoniae serotypes. Given linkage between the capsular biosynthesis locus and two penicillin binding proteins, we tested whether capsule homology increases transformation rates of penicillin resistance. Transformation rates in homologous donor-recipient pairs were no higher than expected, falsifying this hypothesis.